Self-standing chitosan films as dielectrics in organic thin-film transistors - Morgado, J.
Organic thin film transistors, using self-standing 50 gin thick chitosan films as dielectric, are fabricated using sublimed pentacene or two conjugated polymers deposited by spin coating as semiconductors. Field-effect inobilities are found to be similar to values obtained with other dielectrics and, in the case of pentacene, a value (0.13 cm(2)/(V.S) comparable to high performing transistors was determined. In spite of the low On/Off ratios (a maximum value of 600 was obtained for the pentacene-based transistors), these are promising results for the area of sustainable organic electronics in general and for biocoinpatible electronics in particular.